Hotel "Korzo" in the оld core of Peć – a representative example of secession in russian architecture in the territory of Kosovo and Metohija - Ljubenov, Gorica (Arhitektura i urbanizam, 2025)
The architecture of Peć, a city located in the Metohija basin at the foot of the Prokletije mountains, reflects a strong influence of the Oriental style, which dominated its historical construction. However, during the interwar period, the city's central area underwent an architectural transformation influenced by contemporary European trends, resulting in the introduction of modern building elements inspired by early 20th-century architecture. One of the most representative examples from this period is the Korzo Hotel, built in 1929 by Peć merchant Aleksandar Aco Marković. The trapezoidal-shaped building is integrated into the urban context through multi-story structures arranged along radial streets leading to the central square. Its narrower, main facade exhibits stylistic features of Art Nouveau, while the side facades are symmetrical and align with the neighboring buildings. At the end of the 20th century, the hotel was renovated and expanded, yet the fundamental architectural features and elements of Art Nouveau decorative sculpture were preserved. Today, this building represents a significant example of architectural heritage preservation within the context of Peć’s urban development, standing as a testament to the transformations of the city's architectural character throughout the 20th century.
Keywords: Art Nouveau in Russian Architecture; facade design; Korzo Hotel; Peć; Metohija